EFEKTIVITAS MODEL PROBLEM POSING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI SMP NEGERI 3 ANGKOLA SELATAN - Ester Cronica Ritonga (JURNAL MathEdu (Mathematic Education Journal), 2018)
This study aims to know whether there is a significant effectiveness of using problem posing model on students’ mathematical problem solving ability at the seventh grade students of SMP Negeri 3 Angkola Selatan. The research was conducted by using experimental method with 32 students as the sample and they were taken by using cluster sampling technique. Test and observation were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using problem posing model was 3.75 (very good category) and b) the average of students’ mathematical problem solving ability before using problem posing model was 51.87 (fair category) and after using problem posing model was 74.37 (good category). Furthermore, based on inferential statistic by using pair sample ttest and heilpin SPSS version 16, it could be found the significant value was less than 0.05 (0.000<0.05). It means, there is a significant effectiveness of using problem posing model on students’ mathematical problem solving ability at the seventh grade students of SMP Negeri 3 Angkola Selatan.